Biology : understanding life - Alters, Sandra (St. Louis : Mosby, 1996)
Science General
Keywords: Biology; Chemistry; Cell structure; Human biology; Human genetics; Human reproduction; Human evolution; Organism diversity; Social behavior; Ecology; Biosphere